Life Cycle Assessment of Lithium-ion Batteries for Plug-in Hybrid Buses - Olofsson, Ylva; Romare, Mia (My University, 2013)
Electrified buses are becoming increasingly popular and are labeled less environmental impacting compared to conventional buses thanks to reductions in fuel consumption. It is in light of this, however, important to consider the added environmental burden related to production, use, and end of life of the energy storage system, a fundamental component in the electric drive line. This thesis investigates the possible gains and losses when using battery cells with a range of different chemistries. The effect of modularization and change in pack design of the system is also assessed in terms of potential gains and environmental burden. The goal has been to determine the steps in the life cycle with most environmental impact by conducting a life cycle analysis on a full energy storage system based on lithium-ion chemistries. Lithium iron phosphate and lithium nickel manganese cobalt oxide are considered for the cradle to gate life cycle assessment. Other current and future chemistries are assessed for reference. When considering modularization, special focus has been given the environmental impacts related to measures for interoperability of battery module units, as well as effects of reuse and second life. For the use phase, the impacts of the battery related to the number of passengers of the bus are investigated. Also the environmental effect of choosing different battery pack materials is investigated. Regarding the effects of changing cell chemistry, the results indicate that a transition from materials with scarce constituents to those with more abundant materials can be beneficial for the environmental impact, even if energy consumption is not improved. The assessment also pinpoints aluminum current collectors as a part with large impact. In addition, another large part of the impact from the cells is due to the active materials and their processing, indicating the potential gains associated with improved recycling. It is indicated that different processing alternatives have different benefits depending on whether or not the active materials need to be of nano-size. In the perspective of the whole battery pack, the cells together with the electronics and control systems have the largest impacts, and this can efficiently be reduced by applying reuse. Through modularization, the battery pack can be prepared for different types of reuse or second life. When using several small packs the impacts are higher than when using one larger pack. The impact of using several smaller packs is also dependent on the placement of control units. Additional cooling system structure for fast charging has shown to have high significance for the weight of the battery pack, indicating the need of paying high attention to the cooling system design. The electronics and battery monitoring system result in a large impact. The magnitude of this impact is, however, still dependent on the type of printed circuit board used. In the total life cycle, the energy consumption during the driving related to a typical increase in the battery pack weight is same order of magnitude as the energy needed to produce the battery. Moreover, if a weight increase also leads to a decreased passenger capacity, normalizing with the number of passengers has a great importance for the outcome of the LCA, motivating a thorough allocation method. In light of the results found in this thesis it is clear that assessing the impacts of using different materials and components in the battery energy storage system is a key in order to design systems with as low environmental impact as possible.
Keywords: Fysik; Miljövetenskap; Physical Sciences; Environmental Sciences